2014
DOI: 10.1039/c4nj00620h
|View full text |Cite
|
Sign up to set email alerts
|

Probing the self-aggregation behavior and counter ion distribution of a copper surfactant complex

Abstract: The aggregation behavior of the metallosurfactant is pointing towards negative adsorption of metal ions at the micelle surface and surface adsorbed film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Metallosurfactants creates supramolecular arrangements such as micelles, 32 vesicles, 33 reverse vesicles 34 and hybrid crystal with layered perovskite structure. 36,37 It has been observed that location of metal ion in the metallomicelle is very crucial in deciding its further application e.g. 36,37 It has been observed that location of metal ion in the metallomicelle is very crucial in deciding its further application e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallosurfactants creates supramolecular arrangements such as micelles, 32 vesicles, 33 reverse vesicles 34 and hybrid crystal with layered perovskite structure. 36,37 It has been observed that location of metal ion in the metallomicelle is very crucial in deciding its further application e.g. 36,37 It has been observed that location of metal ion in the metallomicelle is very crucial in deciding its further application e.g.…”
Section: Introductionmentioning
confidence: 99%
“…35 Both hydrophobic-and hydrophilic-metal embedded surfactants (in head group and as counter ions) have been synthesized and characterized in the past. 36,37 It has been observed that the location of metal ions in the metallomicelle is crucial in deciding its further applications; for instance, for an effective catalytic cycle, the metal ion should be at the periphery to facilitate facile transfer rather than present at the micelle core. 38 Such abilities prompted us to elicit interactions between uorescein dye and surfactant-containing metal ions to modulate the photophysical properties of photosensitizers in the microheterogeneous environment.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Metallosurfactants of this type are similar to bolaforms; (iii) in type 3 metallosurfactants, the metal complex forms the counterion. [37][38][39][40][41][42][43][44][45][46][47][48][49] The magnetic surfactants, viz. DTAX and C 10 mimY (DTA ¼ dodecyltrimethylammonium cation, C 10 mim ¼ 1-decyl-3-methyl imidazolium cation, X ¼ [GdCl 3 Br] À or [HoCl 3 Br] À or [CeCl 3 Br] À or [FeCl 3 Br] À and Y ¼ [GdCl 4 ] À or [HoCl 4 ] À or [CeCl 4 ] À or [FeCl 4 ] À ), synthesized by Eastoe and co-workers 48,49 fall under this category.…”
Section: Introductionmentioning
confidence: 99%
“…A similar conclusion was reported by Kaur et al when studying the organization of metal ions in DTA[CuBrCl 2 ] at the air/solution and micelle/solution interfaces. 56 …”
Section: Resultsmentioning
confidence: 99%
“…A similar conclusion was reported by Kaur et al when studying the organization of metal ions in DTA-[CuBrCl 2 ] at the air/solution and micelle/solution interfaces. 56 Understanding the impact of metal ions on micelles' size and zeta potential is crucial for optimizing their performance in various applications. The ζ potential is an important indicator of stability for colloidal systems.…”
Section: Synthesis Of Dimeric Metallosurfactants (12−2−12)[mbr 4 ]mentioning
confidence: 99%